Infant Crying, Sleeping, and Feeding Problems in Times of Societal Crises: The Mediating Role of Parenting Stress on Parenting Behavior in Fathers and Mothers - Katharina Richter; Anna Friedmann; Volker Mall; Michaela Augustin (Children)
Background/Objectives: Infant regulatory problems (RPs), i.e., crying, sleeping, and feeding problems, are associated with unfavorable outcomes in later childhood. RPs increased during the pandemic; however, their occurrence in the face of today’s societal challenges remains unclear. RPs are strongly linked to parenting stress and less positive parenting behaviors, but their interplay is less investigated. Methods: In this cross-sectional, questionnaire-based study (ntotal = 7039), we compared the incidences of crying, sleeping, and feeding problems in infants (0–2 years) in pandemic (npandemic = 1391) versus post-pandemic (npost-pandemic = 5648) samples in Germany. We also investigated the relationship between post-pandemic infant RPs and parenting behaviors with parenting stress as a potential mediator for fathers and mothers. Results: Crying/whining/sleeping problems (34.8%) and excessive crying (6.3%) were significantly more prevalent in the post-pandemic sample. In both mothers and fathers, infant RPs were significantly associated with less positive parenting behaviors. Parenting stress partially mediated this relationship. Conclusions: RPs in the post-pandemic era are even more prevalent than during the pandemic, highlighting the imperative for health care professionals to focus on infant mental health. Parenting stress emerges as an entry point for addressing the cycle of infant RPs and maladaptive behaviors in both fathers and mothers.